2013
DOI: 10.1002/cncr.28029
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic and gene expression features of metastatic melanomas to the brain

Abstract: Background The prognosis of MBM is variable with prolonged survival in a subset. It is unclear whether MBMs differ from extracranial metastases (EcM) and primary melanomas (PrM). Methods To study the biology of MBM we performed histopathologic analysis of tumor blocks from patients' craniotomy samples and whole genome expression profiling (WGEP) with confirmatory immunohistochemistry (IHC). Results Mononuclear infiltrate and low intratumoral hemorrhage were associated with prolonged overall survival (OS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 26 publications
(46 reference statements)
3
41
0
Order By: Relevance
“…The risk of BM remains a concern and in fact occurs with a higher incidence as patients with extracranial metastases achieve increasingly longer survival. However, the similar biology of extracranial and brain metastases and equivalent responses following MAPKi have lessened the apparent significance of when metastases involve the brain [26, 34,35]. Patients may also benefit from other mechanisms of MAPKi therapy even after their disease has progressed [36], and ongoing work is elucidating complementary approaches to MAPKi resistance, including co-targeting of the PI3K/AKT signaling pathway [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of BM remains a concern and in fact occurs with a higher incidence as patients with extracranial metastases achieve increasingly longer survival. However, the similar biology of extracranial and brain metastases and equivalent responses following MAPKi have lessened the apparent significance of when metastases involve the brain [26, 34,35]. Patients may also benefit from other mechanisms of MAPKi therapy even after their disease has progressed [36], and ongoing work is elucidating complementary approaches to MAPKi resistance, including co-targeting of the PI3K/AKT signaling pathway [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Good ( Jung et al, 2013;Wansom et al, 2012) Poor Wolf et al, 2015) Poor Good ( Interestingly, some studies have assessed this correlation also in the metastatic sites and have consistently found that increased CD8 + T-cell densities correlated with prolonged OS in CRC liver (Brunner et al, 2014;Katz et al, 2013;Liu et al, 2012;Yoon et al, 2012), lung metastases (Remark et al, 2013), and CNS melanoma metastases (Hamilton et al, 2013;Kluger et al, 2015) (Table 1 and (Table 1 and Fig. 2).…”
Section: )mentioning
confidence: 96%
“…For example, Hamilton et al studied 26 matched brain and extra-cerebral metastases for gene expression profiling and found differences in pathways associated with T cell activity (16). …”
Section: Introductionmentioning
confidence: 99%